Corruption as a driver of Money Laundering in Pakistan - Munawar, Ibtisam (My University, 2023)
The thesis attempted to address the issue of how money laundering in Pakistan is influenced by corruption. Hence the main research question formulated was how does corruption drive money laundering in Pakistan? Connection between corruption and the markets where illicit funds can be exploited and laundered was investigated through a study of the literature and an assessment of recent news. As money laundering and corruption is not easy to trace for a student, so secondary data analysis approach was taken to research on money laundering and corruption in general and specifically from Pakistan’s angle. To answer the main research question, two sub-questions were formulated after finishing the literature review. Money laundering in Pakistan has been discovered to be heavily dependent on the real estate market and the hawala/hundi systems. Hence, two sub- questions formulated were related to real-estate market, how corrupt practices in real-estate drive money laundering? Since there is a dearth of documentation in the real estate market, illegal and legitimate funds can mix, finishing the money-laundering process through under-invoicing. Real- estate market is uses under-invoicing to support money generated from corruption, tax-evasion, vague property valuation, and documentation gap. It is easy to obscure the ownership because of poor documentation, which can easily be used to launder money. The mechanism which helps real-estate market was yet to be found, and here second sub-question was formulated, which is how hawala/hundi is used as a mechanism to promote money laundering in real-estate market? Hawala/hundi system does not use conventional banking methods; it simply moves money. The hawala/hundi mechanism is ideally suited for money laundering because it avoids traditional banking channels, is purely a cash-based occurrence, and is popular among foreigners looking to benefit from a quick, inexpensive, and favourable exchange rate. The hawala/hundi money- laundering system is like a dream come true for businesses that deal in currency. The use of hawala/hundi methods is encouraged by corrupt real estate market practices, making it harder to track down the mixing of illicit and legitimate funds. To effectively control money laundering the thesis managerially contributes by offering solutions to the Pakistani government, which the Pakistani government must adopt to control money laundering and corruption. Developed countries have controlled money laundering and corruption by applying anti-money laundering laws effectively with the help of 40 recommendations proposed by financial action task force. Developed countries have also implemented updated laws and protocols by using digital systems and by removing human involvement from the processes. Increased transparency, capacity building, international cooperation, strict regulatory frameworks, and a strong legal system has also been implemented by developed countries to control money laundering, corruption and related crimes. Pakistan needs to follow the footsteps of developed countries to successfully control corruption and money laundering. Initiatives like Roshan Digital Account, and these efforts ought to be encouraged and road to digitalisation must be followed.
Keywords: Money Laundering, Corruption